Pelatihan RJP terhadap Pengetahuan pada Remaja Anggota Pramuka di Kabupaten Musi Rawas Tahun 2023 - Wahyu Dwi Ari Wibowo; Sapondra Wijaya; Susmini Susmini; Bambang Soewito; Sri Martini; Tri Anggraini (Jurnal Keperawatan Silampari, 2023)
This study aims to identify the effect of CPR training on the level of knowledge of CPR in HJLRS victims. The research method used in this research is quantitative research, with a quasi-experimental approach and pre-test and post-test design. The results showed that after the CPR training, there was an average increase in knowledge from 4.11 (SD Â± 0.994) to 8.52 (SD Â± 0.975), with the results of the Wilcoxon statistical test (p <0.005) (Z value = -6.999). In conclusion, CPR training has proven effective in increasing knowledge of CPR management for HJLRS victims. Keywords: Training, Knowledge, Scouts, CPR